Dual Structural Design of Platinum‐Nickel Hydrogels for Wearable Glucose Biosensing with Ultrahigh Stability. Issue 16 (29th January 2023) - Li, Guanglei; Wang, Chenxin; Chen, Yao; Liu, Fei; Fan, Haoxin; Yao, Bin; Hao, Jia; Yu, Yiting; Wen, Dan
Abstract: Wearable glucose sensors are of great significance and highly required in mobile health monitoring and management but suffering from limited long‐term stability and wearable adaptability. Here a simultaneous component and structure engineering strategy is presented, which involves Pt with abundant Ni to achieve three‐dimensional, dual‐structural Pt‐Ni hydrogels with interconnected networks of PtNi nanowires and Ni(OH)2 nanosheets, showing prominent electrocatalytic activity and stability in glucose oxidation under neutral condition. Specifically, the PtNi(1:3) dual hydrogels shows 2.0 and 270.6 times' activity in the glucose electro‐oxidation as much as the pure Pt and Ni hydrogels. Thanks to the high activity, structural stability, good flexibility, and self‐healing property, the PtNi(1:3) dual gel‐based non‐enzymatic glucose sensing chip is endowed with high performance. It features a high sensitivity, an excellent selectivity and flexibility, and particularly an outstanding long‐term stability over 2 months. Together with a pH sensor and a wireless circuit, an accurate, real‐time, and remote monitoring of sweat glucose is achieved. This facile design of novel dual‐structural metallic hydrogels sheds light to rationally develop new functional materials for high‐performance wearable biosensors. Abstract : Taking the advantages of high activity, structural stability, and good flexibility, the PtNi(1:3) dual hydrogel composed of the interconnected networks of Pt‐Ni nanowires and Ni(OH)2 nanosheets is applied to construct the sensing chip of the wearable glucose sensor, which features a high sensitivity, an excellent selectivity and flexibility, as well as an outstanding long‐term stability of 2 months.